2014
DOI: 10.3109/00365521.2014.934909
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of endoscopic ultrasound-guided fine-needle aspiration for the diagnosis of pancreatic neuroendocrine tumors based on the World Health Organization classification

Abstract: EUS-FNA with a 22-gauge needle is a safe and highly accurate technique for the diagnosis of pNET. There was a clear correlation between the Ki67LI of histological specimens acquired by EUS-FNA and surgery. EUS-FNA with a 22-gauge needle is useful to predict the WHO classification of pNET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 46 publications
(57 reference statements)
4
55
2
Order By: Relevance
“…We could confirm the study by Unno et al [16] which has already elaborated on the importance of tumour size. When using the 5% cut-off, we showed that among the 22 tumours measuring <20 mm, 21 (95.5%) had a concordant grade between cytology and histology.…”
Section: Progression-free Survivalsupporting
confidence: 80%
See 4 more Smart Citations
“…We could confirm the study by Unno et al [16] which has already elaborated on the importance of tumour size. When using the 5% cut-off, we showed that among the 22 tumours measuring <20 mm, 21 (95.5%) had a concordant grade between cytology and histology.…”
Section: Progression-free Survivalsupporting
confidence: 80%
“…When excluding the FNAs where <200 cells were available for counting, the correlation coefficient was r = 0.574, and when 2,000 cells were counted, the correlation became strong with r = 0.824. These values correspond to those found in the literature where concordance varies between 44 and 89% and the κ coefficient between 0.29 (feeble) and 0.82 (strong) [16,24]. This implies that although we could not define cut-offs between grades, absolute values nicely correlate between Ki67-LI on FNA and resection specimens when counting a maximum of cells on our routine clinical material, confirming the study by Hasegawa et al [15].…”
Section: Progression-free Survivalsupporting
confidence: 79%
See 3 more Smart Citations